Sinergi Pentahelix untuk Pembangunan Berkelanjutan: Pemberdayaan Masyarakat melalui Program KKN-PMM di Kelurahan Tonja - Anak Agung Istri Pradnyarani Dewi; Putu Yudha Asteria Puteri; I Gede Nyoman Carlos W. Mada (Journal of Social Service and Empowerment, 2025)
ABSTRACT Sustainable development is a global agenda that requires multi-stakeholder involvement in integrating economic, social, and environmental dimensions. The pentahelix collaboration model—engaging government, business, academia, communities, and the media—has proven to be an effective strategy in accelerating the achievement of the Sustainable Development Goals (SDGs). The Community Service Program (Kuliah Kerja Nyata – Program Pemberdayaan Masyarakat, KKN-PMM) of Warmadewa University in Kelurahan Tonja, North Denpasar, was designed to implement pentahelix synergy through four main pillars: physical health, mental health, financial well-being, and environmental preservation. The implementation methods included observation, participatory training, mentoring, and joint community actions. The results indicate increased awareness and participation among residents in maintaining health, managing MSME finances through simple bookkeeping, utilizing digital marketing, and actively engaging in environmental cleanliness initiatives. Cross-sector synergy has strengthened social cohesion, encouraged local innovation, and created a sustainable empowerment model. This program contributes theoretically by enriching the literature on pentahelix-based community empowerment and practically by serving as a reference for developing thematic community service programs in higher education to support the achievement of SDGs at the local level. Keywords: pentahelix, sustainable development, community empowerment, KKN-PMM, SDGs.   ABSTRAK Pembangunan berkelanjutan merupakan agenda global yang menuntut keterlibatan multipihak dalam mengintegrasikan dimensi ekonomi, sosial, dan lingkungan. Model kolaborasi pentahelix—yang melibatkan pemerintah, dunia usaha, akademisi, komunitas, dan media—telah terbukti menjadi strategi efektif dalam mendorong percepatan capaian Sustainable Development Goals (SDGs). Kegiatan Kuliah Kerja Nyata – Program Pemberdayaan Masyarakat (KKN-PMM) Universitas Warmadewa di Kelurahan Tonja, Denpasar Utara, dirancang untuk mengimplementasikan sinergi pentahelix dalam empat pilar utama: kesehatan fisik, kesehatan mental, kesejahteraan finansial, dan pelestarian lingkungan. Metode pelaksanaan meliputi observasi, pelatihan partisipatif, pendampingan, dan aksi nyata bersama masyarakat. Hasil kegiatan menunjukkan peningkatan kesadaran dan partisipasi warga dalam menjaga kesehatan, mengelola keuangan UMKM secara sederhana, memanfaatkan pemasaran digital, serta berperan aktif dalam kegiatan kebersihan lingkungan. Sinergi lintas sektor memperkuat kohesi sosial, mendorong inovasi lokal, dan membentuk model pemberdayaan yang berkelanjutan. Program ini memberikan kontribusi teoretis berupa penguatan literatur pemberdayaan berbasis pentahelix serta kontribusi praktis sebagai acuan pengembangan KKN tematik di perguruan tinggi untuk mendukung pencapaian SDGs di tingkat lokal. Kata kunci: pentahelix, pembangunan berkelanjutan, pemberdayaan masyarakat, kuliah kerja nyata, SDGs.